Trunk muscle dysfunction in patients with myotonic dystrophy type 2 and its contribution to chronic low back pain - Vlazna, Daniela; Krkoska, Peter; Sladeckova, Michaela; Parmova, Olesja; Barusova, Tamara; Hrabcova, Karolina; Vohanka, Stanislav; Matulova, Katerina; Adamova, Blanka (Frontiers in Neurology, 2023)
Introduction Myotonic dystrophy type 2 (MD2) presents with a varied manifestation. Even though the myopathy in these patients is more widespread, axial musculature involvement is one of the most prominent conditions. MD2 patients also often report chronic low back pain (CLBP). The purpose of this study was to evaluate trunk muscle function, including respiratory muscles, in patients with MD2 and to compare it with healthy controls, to determine the occurrence of CLBP in patients with MD2, and to assess whether trunk muscle dysfunction increases the risk of CLBP in these patients. Methods We enrolled 40 MD2 patients (age range 23 to 76 years, 26 women). A comprehensive battery of tests was used to evaluate trunk muscle function. The tests consisted of quantitative muscle strength testing of low back extensor muscles and respiratory muscles and the assessment of trunk muscle endurance. A neurological evaluation contained procedures assessing the distribution of muscle weakness, myotonia, and pain, and used questionnaires focused on these items and on disability, depression, and physical activity. Results The results of this study suggest that patients with MD2 show significant dysfunction of the trunk muscles, including the respiratory muscles, expressed by decreased muscle strength and endurance. The prevalence of CLBP in patients with MD2 was 52.5%. Based on our analysis, the only independent significant risk factor for CLBP in these patients was maximal isometric lower back extensor strength in a prone position ≤ 15.8 kg (OR = 37.3). Other possible risk factors were severity of myotonia and reduced physical activity. Conclusion Outcomes of this study highlighted the presence of axial muscle dysfunction, respiratory muscle weakness, and frequent occurrence of CLBP together with its risk factors in patients with MD2. We believe that the findings of this study may help in management and prevention programs for patients with MD2.